Diseño de un marco de referencia para el emprendimiento de negocios de TI basado en la filosofía "Lean Startup" - Ordoñez Ortiz, Johnny Fabricio (2014)
As a society, it is has a number of techniques proven for managing large companies and known to be the best practices in creating products. But these practices do not work when it is about information technologys products and services; they are instead characterized by chaos and uncertainty. The establishment of a new enterprise or StartUp requires management. This may surprise aspiring entrepreneurs, because their conceptions of these two words are diametrically opposed. The entrepreneurs are, firstly, cautious when implementing traditional practices to manage a StartUp company. They fear that these practices will lead to bureaucracy or will suppress creativity; therefore, Lean StartUp is dedicated to preventing these problems...